Lean Manufacturing Approach to Minimize Waste Production Parts STN Wfx000 RIB at the Prismatic Medium Machine 2 in PT X - Ariffien, Afferdhy; Rosminingsih, Deby (International Review of Management and Marketing, 2017)
In the aircraft industry, generally 75% of the material used to make an aircraft component will be garbage, so we need a system efficiency of production on the other side. The efficiency of production systems that run very influential on the performance of the company. Thus, elimination or minimization of waste that occurs is one solution. The approach can be used to eliminate or minimize waste in a production system is lean manufacturing company. Lean manufacturing is a systematic approach to identify and find the cause of the waste and then minimizing or even eliminating it. This study aims to minimize waste in the production process RIB AT STN WFX000 part name in the area of medium prismatic machine 2. The results of the analysis of waste relationship matrix obtained two types of waste that is inventory and waiting, each of which has a weight 7,143 and 6,28 with detailed mapping tools are chosen process mapping activity with the score 198,286 and supply chain response matrix with a score of 139,429. Keywords: Lean Manufacture, Value Stream Mapping, Value Stream Analysis Tool, SCRM JEL Classifications: L11, L15, L61